CORPORATE GOVERNANCE REFORMS IN STATE-OWNED JOINT STOCK COMPANIES OF UZBEKISTAN: PROGRESS, CHALLENGES, FUTURE DIRECTIONS (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
This article examines the state of corporate governance in state-owned joint stock companies (SOJSCs) in Uzbekistan. Using qualitative analysis based on secondary data from international financial institutions, academic literature, and official reform documents, the study evaluates current governance structures, identifies reforms undertaken since 2016, and discusses remaining challenges in aligning Uzbekistan’s corporate governance practices with OECD principles. The results show that while Uzbekistan has made considerable progress in transparency, IFRS transition, independent directors and capital market readiness, state dominance and political influence over boards and key decisions still limit full autonomy and market discipline. The paper concludes with a balanced assessment of progress and future reform priorities.